2021
DOI: 10.1038/s41598-021-94214-4
|View full text |Cite|
|
Sign up to set email alerts
|

Drug-associated cues and drug dosage contribute to increased opioid seeking after abstinence

Abstract: Patients with opioid use disorder experience high rates of relapse during recovery, despite successful completion of rehabilitation programs. A key factor contributing to this problem is the long-lasting nature of drug-seeking behavior associated with opioid use. We modeled this behavior in a rat drug self-administration paradigm in which drug-seeking is higher after extended abstinence than during the acute abstinence phase. The goal of this study was to determine the contribution of discrete or discriminativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The relapse test contained identical contextual and visual cues used during acquisition; however, active lever presses did not result in any morphine infusions. Consistent with literature on incubation of craving for other opioids (Airavaara et al, 2011;Gyawali et al, 2020;Reiner et al, 2020;Theberge et al, 2013;Zanda et al, 2021), extended forced abstinence from morphine resulted in a time-dependent increase in drugseeking behaviour, as measured by a significant increase in active lever presses at 30D (unpaired t test, 1D vs. 30D relapse test: t(14) = 4.405, p = 0.0006; Figure 1). Subsequent analyses were performed with this experimental group to provide insight into how miRNA expression is affected by cue re-exposure in early and late abstinence.…”
Section: Extended Forced Abstinence Results In Incubation Of Morphine...supporting
confidence: 86%
“…The relapse test contained identical contextual and visual cues used during acquisition; however, active lever presses did not result in any morphine infusions. Consistent with literature on incubation of craving for other opioids (Airavaara et al, 2011;Gyawali et al, 2020;Reiner et al, 2020;Theberge et al, 2013;Zanda et al, 2021), extended forced abstinence from morphine resulted in a time-dependent increase in drugseeking behaviour, as measured by a significant increase in active lever presses at 30D (unpaired t test, 1D vs. 30D relapse test: t(14) = 4.405, p = 0.0006; Figure 1). Subsequent analyses were performed with this experimental group to provide insight into how miRNA expression is affected by cue re-exposure in early and late abstinence.…”
Section: Extended Forced Abstinence Results In Incubation Of Morphine...supporting
confidence: 86%
“…We demonstrated that heroin self-administration of a 0.03 mg/kg dosage can induce regulation of 76 circRNAs in the OFC. This dosage of heroin has been used by many labs to model drug-seeking behavior and we have previously demonstrated that animals that have higher amounts of drug intake at this dosage typically have more drug-seeking behavior after extended forced abstinence [4,51]. However, this dosage does not result in incubation of heroin craving behavior, and we expect that a higher dosage protocol (e.g., 0.075 or 1.0 mg/kg/infusion) may result in an additional unique set of circRNAs specifically associated with long-lasting drug seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…After 5-7 days of acclimation, animals underwent intravenous catheter surgery for heroin or saline self-administration, as previously described [51]. Following surgery, all animals were singly housed for the remainder of the study.…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Immunotherapeutics for substance use disorders (SUD) and overdose have been in preclinical development for some time (e.g., cocaine, heroin and other morphine derivatives, oxycodone, and fentanyl); the current status of vaccine development in the context of SUD is reviewed here (Pravetoni and Comer, 2019). Their development reflects both the acute need for relapse protection measures (the rate of relapse is > 80% after exiting rehabilitation clinics (Smyth et al, 2010; Zanda, Floris and Sillivan, 2021)), and the need for an adjunct to treatment with naloxone, the opioid receptor antagonist which is the current standard of care for reversal of overdose. Unfortunately, the short half-life of naloxone can lead to individuals “re-overdosing” due to “re-narcotization” from the same initial dose of fentanyl (Seth et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%